1999
DOI: 10.1515/ijmsp.1999.2.1.1
|View full text |Cite
|
Sign up to set email alerts
|

A Biaxial Actively Damped Boring Bar for Chatter Mitigation

Abstract: This paper summarizes the development and testing of an actively damped boring bar for mitigation of selfexcited chatter vibrations. PZT stack actuators are integrated into a commercially available bar to provide vibration suppression both normal and tangential to the workpiece surface. Biaxial control is proven essential to obtaining good performance over the normal range of tool mounting variability. Cutting tests performed at various speeds and depths of cut on a hardened steel workpiece illustrate the bar'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…To efficiently use active control to increase system damping, the actuator must be placed at a location which are well matched to the modes to control [6]. A good measure of the effectiveness of an actuator to a given mode is the normalized length of the input shape vector.…”
Section: Application To Critical Speedmentioning
confidence: 99%
“…To efficiently use active control to increase system damping, the actuator must be placed at a location which are well matched to the modes to control [6]. A good measure of the effectiveness of an actuator to a given mode is the normalized length of the input shape vector.…”
Section: Application To Critical Speedmentioning
confidence: 99%
“…Virtual vibration absorbers were successfully implemented for chatter avoidance in turning by Pratt and Nayfeh (1997. Redmond et al (1999), Browning et al (1997), and Nayfeh (1997, 1999) concluded that biaxial control is necessary to ensure satisfactory chatter suppression. Nachtigal (1972) proposed a feed-forward approach for control of chatter in the lathe and Glaser and Nachtigal (1979) extended it to boring operations.…”
Section: Introductionmentioning
confidence: 99%
“…The resonator is an active vibration absorber tuning achieved by utilizing a simple time-delayed feedback. Redmond et al (1999) proposed a biaxial actively damped boring bar for chatter mitigation. Chung et al (1997) investigated active damping of structural models in high-speed machine tools.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of the use of active systems to alter dynamics during machining are relatively few, see Comstock, Tse, and Lemon, 1969, Sadek and Tobias, 1973, Hong-Yeon Hwang, Jun-Ho Oh, and Kwang-Joon Kim, 1988, and Shiraishi, Yamanaka, and Fujita, 1990, General Dynamics Team 1998, and Redmond, Barney, and Smith, 1999. In general, most of these papers address turning, not milling.…”
Section: Introductionmentioning
confidence: 99%